1999
DOI: 10.1046/j.1523-1739.1999.98445.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Landscape Composition and Wetland Fragmentation on Frog and Toad Abundance and Species Richness in Iowa and Wisconsin, U.S.A.

Abstract: Management of amphibian populations to reverse recent declines will require defining high‐quality habitat for individual species or groups of species, followed by efforts to retain or restore these habitats on the landscape. We examined landscape‐level habitat relationships for frogs and toads by measuring associations between relative abundance and species richness based on survey data derived from anuran calls and features of land‐cover maps for Iowa and Wisconsin. The most consistent result across all anura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
197
4
35

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(249 citation statements)
references
References 41 publications
13
197
4
35
Order By: Relevance
“…In our case, landscape variables had only a minor effect on the assembly of communities. In a less fragmented landscape like our study area, forests can moderate the negative effects of intensive agriculture (Hartel et al 2010;Knutson et al 1999). Sheltered corridors with moist microclimate and wet substrate are very important during dispersal, especially for recently metamorphosed juveniles to avoid dehydration (Gibbs 1998).…”
Section: Relative Importance Of Metacommunity Processesmentioning
confidence: 99%
“…In our case, landscape variables had only a minor effect on the assembly of communities. In a less fragmented landscape like our study area, forests can moderate the negative effects of intensive agriculture (Hartel et al 2010;Knutson et al 1999). Sheltered corridors with moist microclimate and wet substrate are very important during dispersal, especially for recently metamorphosed juveniles to avoid dehydration (Gibbs 1998).…”
Section: Relative Importance Of Metacommunity Processesmentioning
confidence: 99%
“…A temperatura elevada e a baixa umidade encontrada em áreas abertas devem ser limitantes para anfíbios, que apresentam alta taxa de perda de água por evaporação e pouca habilidade de dispersão (Rothermel & Semlitsch 2002). Neste contexto, fragmentos florestais são hábitats relativamente menos perturbados em comparação com áreas agrícolas e urbanas, e proporcionam corredores para migração de anuros entre sítios de reprodução e áreas de refúgio, alimentação e estivação (Laan & Verboom 1990, Knutson et al 1999, Weyrauch & Gubb Jr. 2004.…”
Section: Introductionunclassified
“…Previous studies have found that wetland characteristics alone are insufficient to explain variations in amphibian species richness and that landscape characters (e.g., surrounding land use) are also important (Hecnar and MCloskey 1996;Knutson et al 1999). In our study, restored and reference wetlands are situated in an agriculturallydominated landscape, and are surrounded by similar buffers of perennial vegetation.…”
Section: Amphibian Characteristicsmentioning
confidence: 99%